Bedaquiline has potential for targeting tuberculosis reservoirs in the central nervous system. Issue 22 (28th March 2018) - Pamreddy, Annapurna; Baijnath, Sooraj; Naicker, Tricia; Ntshangase, Sphamandla; Mdanda, Sipho; Lubanyana, Hlengekile; Kruger, Hendrik G.; Govender, Thavendran
Abstract : Bedaquiline (BDQ) was administered to healthy Sprague-Dawley rats in order to determine its localisation in the brain using mass spectrometry imaging (MSI). This study shows that BDQ has the potential for targeting TB reservoirs in the CNS. Abstract : Bedaquiline (BDQ) is the first-in-class United States Food and Drug Administration (US FDA) approved anti-tuberculosis (anti-TB) drug, which is a novel diarylquinoline antibiotic that has recently been utilized as an effective adjunct to existing therapies for multidrug-resistant tuberculosis (MDR-TB). BDQ is especially promising due to its novel mechanism of action, activity against drug-sensitive and drug-resistant tuberculosis (TB) in addition to having the potential to shorten treatment duration. Drug delivery to the central nervous system (CNS) is a major concern in TB chemotherapy, especially with the increasing cases of CNS-TB. In this study, we investigated the CNS penetration of BDQ in healthy rodent brain. Male Sprague-Dawley rats ( n = 27; 100 ± 20 g) received a single 25 mg kg −1 b.w dose of BDQ via intraperitoneal (i.p.) administration, over a 24 h period. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to determine whole tissue drug concentrations and matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) was utilized to evaluate drug distribution in the brain. BDQ reached peak concentrations ( C max ) of 134.97 ng mL −1 in the brain at a T max of 4 h, which is within the range required for therapeutic efficacy. BDQ was widely distributed in the brain, with a particularly high intensity in the corpus callosum and associated subcortical white matter including the striatal, globus pallidus, corticofugal pathways, ventricular system, basal forebrain region and hippocampal regions. Using MALDI MSI, this study demonstrates that due to BDQ's distribution in the brain, it has the potential to target TB reservoirs within this organ.